2021
DOI: 10.1002/alz.12506
|View full text |Cite
|
Sign up to set email alerts
|

Normal cerebrospinal fluid concentrations of PDGFRβ in patients with cerebral amyloid angiopathy and Alzheimer's disease

Abstract: Background: Cerebrospinal fluid (CSF) platelet‐derived growth factor receptor‐β (PDGFRβ) has been proposed as a biomarker of blood–brain barrier (BBB) breakdown. We studied PDGFRβ levels as a biomarker for cerebral amyloid angiopathy (CAA), amnestic mild cognitive impairment (aMCI), or Alzheimer's disease (AD). Methods: CSF PDGFRβ levels were quantified by enzyme‐linked immunosorbent assay in patients with CAA, patients with aMCI/AD, and in matched controls. In aMCI/AD we evaluated CSF PDGFRβ both by clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…In contrast to our findings, increases in CSF PDGFR concentrations have been observed in AD defined clinically or by A/T/N classification 3,9,10,24,30 . The lack of association between CSF PDGFR and A status and A or tau biomarkers was observed previously 3,5,9,10,24 , although one study showed that A burden modulated the association of PDGFR with Tau-PET 31 . Other authors also did not find an association between PDGFR and small vessel disease in cerebral amyloid angiopathy (CAA) subjects 9 .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our findings, increases in CSF PDGFR concentrations have been observed in AD defined clinically or by A/T/N classification 3,9,10,24,30 . The lack of association between CSF PDGFR and A status and A or tau biomarkers was observed previously 3,5,9,10,24 , although one study showed that A burden modulated the association of PDGFR with Tau-PET 31 . Other authors also did not find an association between PDGFR and small vessel disease in cerebral amyloid angiopathy (CAA) subjects 9 .…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of association between CSF PDGFR and A status and A or tau biomarkers was observed previously 3,5,9,10,24 , although one study showed that A burden modulated the association of PDGFR with Tau-PET 31 . Other authors also did not find an association between PDGFR and small vessel disease in cerebral amyloid angiopathy (CAA) subjects 9 . The existing literature has important differences from our study that need to be considered.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations